2009
DOI: 10.1103/physreva.79.063814
|View full text |Cite
|
Sign up to set email alerts
|

Orientation ofNd3+dipoles in yttrium aluminum garnet: Experiment and model

Abstract: We report an experimental study of the 1.064 µm transition dipoles in neodymium doped yttrium aluminium garnet (Nd-YAG) by measuring the coupling constant between two orthogonal modes of a laser cavity for different cuts of the YAG gain crystal. We propose a theoretical model in which the transition dipoles, slightly elliptic, are oriented along the crystallographic axes. Our experimental measurements show a very good quantitative agreement with this model, and predict a dipole ellipticity between 2% and 3%. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
16
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 18 publications
6
16
0
Order By: Relevance
“…1(a). As expected, for this orientation which is close to = 0° and for which the coupling is expected to be minimum [2], the anti-phase peak becomes so small that it disappears below the noise floor.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…1(a). As expected, for this orientation which is close to = 0° and for which the coupling is expected to be minimum [2], the anti-phase peak becomes so small that it disappears below the noise floor.…”
Section: Introductionsupporting
confidence: 80%
“…The nonlinear coupling constant in this laser being adjustable, we present how the spectral correlation between the intensity noises of the two orthogonally polarized modes behaves according to the coupling constant. It is has recently been shown that, in Nd:YAG, the emitting dipoles behave as if they were aligned along the crystallographic axes of the matrix [2]. In particular, by choosing a (100)-cut Nd:YAG crystal instead of the more common (111) cut, it was demonstrated that almost complete decoupling of two perpendicularly polarized laser modes could be obtained by aligning them with the (010) and (001) crystallographic axes.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with the fact that the laser behaves as if the emitting dipoles were aligned along the crystallographic axes, like in Ref. [15]. In the interesting situations corresponding to α = −2…”
supporting
confidence: 73%
“…The question now is how should we choose our active medium in order to uncouple the two polarization modes, i. e., in order to minimize cross-saturation effects among our two modes ? It has recently been shown that, in Nd:YAG, the emitting dipoles behave as if they were aligned along the crystallographic axes of the matrix [15]. In particular, by choosing a (100)-cut Nd:YAG crystal instead of the more common (111) cut, it was shown that almost complete decoupling of two perpendicularly polarized modes could be obtained by aligning them with the (010) and (001) crystallographic axes.…”
mentioning
confidence: 99%
“…The influence of Cr:YAG crystal orientation on the generation dynamics was studied in [14,15,16] using PLM. Recently analogous generalization of orientation of Nd 3+ dipoles was proposed for Nd:YAG laser medium [29]. In this paper for the simplicity we will use only parallel orientation of polarization with crystal axis f j (θ) = (ĵê) 2 ≡ 1 and will not take into account the same possibility for Nd 3+ dipoles.…”
Section: Model Descriptionmentioning
confidence: 99%